Descriptive over-representation, cliental accountability, and minority politics: the case of the Druze in Israel. Issue 8 (17th November 2022) - Jamal, Amal
ABSTRACT: This article explores the relationship between descriptive representation, patrimonial voting, turnout, and voting patterns in small ethnic groups. It argues that the combination between patrimonial voting and descriptive representation marginalizes the importance of substantive representation, leading to a decline in turnout, but simultaneously to cliental loyalty networks among voters that shape voting preferences. It utilizes the case of the Druze in Israel and analyzes their voting patterns in order to establish the argument that the mechanism that leads to party preferences among minority voters, namely, clientalistic accountability, is the same mechanism that renders descriptive over-representation devoid of substantive impact on state policies directed towards the minority. Our aim is to enrich the literature on the affinity between minority descriptive representation, patrimonial voting, clientalist accountability, and political efficacy. We demonstrate that Druze candidates in Zionist parties, especially those close to decision-making circles by being part of the governmental coalition, establish a broad network of supporters based on family ties, personally benefiting voters by integrating them or their relatives into high-income jobs, making their cliental preferences rational. This creates the gap between mere descriptive representation of minority groups and the substantial representation of their communal interests in "patronage democracy."